Odpowiedzi

2010-03-04T14:59:57+01:00
4x - 3 = 3x+5
4x-3x=5+3
x=8

b)5x +2 = 7 - 3x
5x+3x= 7-2
8x = 6 |:8
x = 6/8
x=3/4

c)3(x - 1) = 0
3x-3=0
3x=3 |:3
x= 1

d)-6x(x +1) = 24
-6x² -6x = 24
-6x = 24 |:(-6)
x = -4

e)-7(x - 2) = 3x - 1
-7x +14 = 3x-1
14+1= 3x+7x
15 = 10x |:10
x= 15/10
x = 1 5/10
x = 1½

f)4(x - 1 ) = 6(1 + x)
4x-4=6+6x
-4+6=6x-4x
2=2x |:2
x=1
2010-03-04T15:03:33+01:00
A)4x - 3 = 3x+5
4x-3x=5+3
x=8

4*8-3=3*8+5
32-3=24+5
29=29


b)5x +2 = 7 - 3x
5x+3x=7-2
8x=5/:8
x=5/8

5*5/8+2=7-3*5/8
3 i 1/8+2=7- 1 i 7/8
5 i 1/8= 6 i 1/8

c)3(x - 1) = 0
3x-3=0
3x=3/:3
x=1

3(1-1)=0
3-3=0

d)-6x(x +1) = 24
-6x-6x=24
-12x=24/:(-12)
x=-2

-6*-2(-2+1)=24



e)-7(x - 2) = 3x - 1

-7x+14=3x-1
-7x-3x=-1-14
-10x=-15/:(-10)
x=15/10 = 3/2 = 1 i 1/2

-7*1,5+14=3*1,5-1
-10,5+14=4,5-1
3,5=3,5



lixcze na maxa;))

f)4(x - 1 ) = 6(1 + x)
4x-4=6+6x
4x-6x=6+4
-2x=10/:(-2)
x=-5

4(-5-1)=6(1-5)
-20-4=6-30
-24=-24
2 4 2
2010-03-04T15:09:44+01:00
A)4x - 3 = 3x+5
4x - 3x= 5+3
x= 8

spr 4* - 3= 3*8+5

b)5x +2 = 7 - 3x
5x + 3x=7-2
8x=5
x=5/8

spr. 5*5/8 +2= 7-3*5/8

c)3(x - 1) = 0
3x - 3=0
3x= 3
x=1

spr. 3(1-1)= 0

d)-6x(x +1) = 24
-6x² - 6x -24=0 /: (-6)
x² + x + 4=0


Δ= 1- 4*1*4 = -15 brak rozw

e)-7(x - 2) = 3x - 1

-7x+14=3x-1
-10x=-15 / (-10)
x=3/2

sppr. -7(3/2 - 2)=3 * 3/2 -1

f)4(x - 1 ) = 6(1 + x)
4x-4=6+6x
-2x=10/(-2)
x=-5

spr. 4(-5-1)= 6(1-5)

2 5 2